2006
DOI: 10.1136/ard.2005.048975
|View full text |Cite
|
Sign up to set email alerts
|

Are American College of Rheumatology 50% response criteria superior to 20% criteria in distinguishing active aggressive treatment in rheumatoid arthritis clinical trials reported since 1997? A meta-analysis of discriminant capacities

Abstract: Objective: To carry out a meta-analysis designed to compare the discriminant capacities of American College of Rheumatology 50% (ACR50) with 20% (ACR20) responses in clinical trials on rheumatoid arthritis reported after 1997 and to analyse whether ACR50 can be as informative as ACR20 in distinguishing active from control treatments in more recent trials. Methods: Clinical trials on rheumatoid arthritis reported since 1997 were identified, which included aggressive combinations of disease-modifying antirheumat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…Given the relatively high efficacy of the more effective biological DMARDs, ACR20 may not represent the optimal clinical response outcome measure for rheumatologists . In contrast, ACR50 appears to be a better endpoint to distinguish clinically significant treatment effects between treatment arms for contemporary RA trials . Therefore, ACR50 was evaluated in our meta‐analysis.…”
mentioning
confidence: 99%
“…Given the relatively high efficacy of the more effective biological DMARDs, ACR20 may not represent the optimal clinical response outcome measure for rheumatologists . In contrast, ACR50 appears to be a better endpoint to distinguish clinically significant treatment effects between treatment arms for contemporary RA trials . Therefore, ACR50 was evaluated in our meta‐analysis.…”
mentioning
confidence: 99%
“…In recent years, the availability of more efficacious therapies has increased the expectations of benefit of treatment, which has raised the question as to whether the goal of future clinical trials might be levels of improvement higher than ACR20, or even higher than ACR50, or absolute measures of efficacy, such as Disease Activity Score (DAS)12 or ACR criteria for remission 13. However, the definitions that require lower levels of response (ACR20) may be more discriminative between the placebo and the index drug in clinical trials,14 although a recent meta-analysis of 21 clinical trials conducted in adult patients with rheumatoid arthritis has indicated similar discriminant capacities of ACR20 and ACR50 responses 15. Nevertheless, the optimal threshold level of improvement to be used in clinical trials is still uncertain 9…”
mentioning
confidence: 99%
“…It is defined as a 50% improvement in swollen and tender joint counts plus a 50% improvement in 3 of the following 5 criteria: (1) patient global assessment; (2) physician global assessment; (3) pain score; (4) physical function (Health Assessment Questionnaire score) and (5) laboratory acute phase reactants (erythrocyte sedimentation rate or C-reactive protein level). 10 For safety, we sought to include specific adverse events; however, these were reported inconsistently. Therefore, we chose to include withdrawals that occurred because of adverse events, which is a measure of patients' tolerance of adverse events and is reported consistently.…”
mentioning
confidence: 99%
“…Outcomes Two major outcomes were specified a priori: benefit (defined as a 50% improvement in the American College of Rheumatology symptomatic criteria [ACR50]) 10 and safety (determined by the number of withdrawals because of adverse events). ACR50 is a validated clinically meaningful binary measure of benefit.…”
mentioning
confidence: 99%